Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Platinum Jaya Logistic - Pratama, Isa Alfio; Siska, Elmira (Jurnal Mahasiswa Kreatif, 2024)
PT Platinum Jaya Logistic is a company engaged in logistics. Problems related to compensation are that some employees feel that they do not get compensation in accordance with their workload, so they are not maximally motivated to do their job. The purpose of this study was to analyze the effect of compensation and work motivation partially or simultaneously on employee performance at PT Platinum Jaya Logistic. The research method is to apply a quantitative design. Sampling was done with a saturated sample technique of 50 employees. The data processing method starts from the data quality test which consists of validity and reliability tests, classical assumption tests, t tests and F tests. The results of this study indicate that the questionnaire variables are valid and reliable and free from econometric problems. The compensation variable partially affects employee performance at PT Platinum Jaya Logistic is positive and significant. The motivation variable partially influences employee performance at PT. Platinum Jaya Logistic is also positive and significant. Simultaneously, both variables have a positive and significant effect on employee performance at PT Platinum Jaya Logistic. The results of this study can be the basis for developing a broader human resource management strategy, which involves aspects of compensation and motivation as the main key in improving employee performance.